Invasion : the inside story of Russia's bloody war and Ukraine's fight for survival - Harding, Luke, 1968- (Vintage Books, a division of Penguin Random House LLC, 2022)
"In a damning, inspiring, and breathtaking narrative of what is likely to be a turning point for Europe--and the world--Guardian correspondent and New York Times bestselling author Luke Harding reports firsthand on the Russian invasion of Ukraine. When, just before dawn on February 24, 2022, Vladimir Putin launched a series of brutal attacks, Harding was there, on the ground in Kyiv. But this senseless violence was met with astounding resilience--from, among others, the country's embattled president, Volodymyr Zelenskiy--and the courage of a people prepared to risk everything to preserve their nation's freedom." --